Postpartum Uterine Prolapse in a Goat and its Successful Management - Singh, Bhoopendra; Singh, Kaushalendra Pratap; Kumar, Rajesh; Singh, Shubhendra Vikram; Husain, Safayat (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Postpartum uterine prolapse occurs in all animal species. It is most common in cows and ewe, less common in the doe and rare in the mare. It is an eversion of the uterus, which turns inside out as it passes through the vagina. Prolapse of uterus generally occurs immediately after or a few hours of parturition when the cervix is open, and the uterus lacks tone (Hanie, 2006). The prolapse is visible as a large mass protruding from the vulva, often hanging down below the animal’s hock. The etiology of uterine prolapse is not yet fully known. Hormonal imbalance, hypocalcemia, mineral imbalances, injuries or stretching of birth passage, excessive traction at assisted parturition, dystocia or forceful removal of fetal membranes may contribute to the occurrence of prolapse (Hanie, 2006; Jackson, 2004). Animals with uterine prolapse should be treated promptly; otherwise, it may lead to edema, ischemia, laceration, internal hemorrhage (Noakes et al., 2001), prostration, and shock making prognosis poor to hopeless. The success of treatment depends on the type of case, the degree of damage, and contamination. The present case highlights the successful management of postpartum uterine prolapse in a goat.